UPAYA MENINGKATKAN LITERASI BACA TULIS MASYARAKAT - Rahma Muti'ah; Mulkan Ritonga; Budianto Bangun; Harimansyah; Syahrol Sulaiman Ritonga; Dandi Febrianto (Politeknik Negeri Sriwijaya, 2022)
Improving literacy, especially reading and writing literacy in society, must be one of the centers of attention of various parties. Low literacy skills will encourage people to respond incorrectly to information that has the potential to take actions that are not in accordance with existing rules and can even hinder the growth of the global human development index as the government hopes, and can even harm themselves. This service activity is carried out in an effort to improve literacy in village communities. Activities are carried out by means of outreach, discussions and training that directly involve the community. The implementation of this community service activity proves that the discussion, socialization and training methods can improve the literacy skills of the village community. Providing socialization and training materials can encourage the growth of self-confidence in the basic abilities they have, so that people are increasingly aware that with good literacy, they will find it easier to process and socialize in all conditions.